China's changing political landscape prospects for democracy - Li, Cheng, 1956- (Brookings Institution Press, 2008)
"Leading experts examine the prospects for democracy in the world's most populous nation and break down a number of issues in Chinese domestic politics, including changing leadership dynamics, the rise of business elites, increased demand for the rule of law, and shifting civil-military relations"--Provided by publisher.